Establishing and Validating: A DOE Approach of a Novel Quantitative Method for the Simultaneous Estimation of Methotrexate, Curcumin, and Etodolac Using RP-HPLC Method - Singh, Jitendra Pratap; Singh, Deepak; Tiwari, Gaurav (International Journal of Pharmaceutical Investigation, 2026)
Background It is very hard to measure Methotrexate (MTX), $(CUR), and Etodolac (ETO) all at the same time because they have very different chemical and physical qualities and might work well together in inflammation and cancer treatments. Objectives The goal is to create and test a reliable Reverse-Phase High-Performance Liquid Chromatography (RP-HPLC) method for measuring MTX, CUR, and ETO at the same time using the Design of Experiments (DOE) method for method improvement. Materials and Methods A full DOE approach using Box-Behnken design was used to find the best chromatographic conditions, such as the makeup of the mobile phase, the flow rate, and the temperature of the column. The method was checked against the ICH Q2(R1) standards for linearity, specificity, accuracy, reliability, and stability. Results The best method achieved baseline separation with retention times of 3.2±0.1 min for MTX, 8.7±0.1 min for CUR, and 12.4±0.1 min for ETO. We made linear calibration curves for concentrations of 5 to 50 μg/mL of MTX, 10 to 100 μg/mL of CUR, and 25 to 250 μg/mL of ETO. The correlation coefficients (r²) were all greater than 0.999. The method worked very well, with an RSD of less than 2.0% and an accuracy range of 98-102% for all analytes. Conclusion The RP-HPLC method that was created is a strong, accurate, and reliable way to measure the amounts of MTX, CUR, and ETO all at the same time. It can be used for bioanalytical and pharmaceutical quality control.
Keywords: Methotrexate; Curcumin; Etodolac; RP-HPLC; Design of Experiments; Method Validation; Simultaneous Estimation.